Les sanctuaires arvernes et vellaves hors des chefs-lieux de cités du ier s. av. J.-C. au ive s. ap. J.-C. : approche typologique et spatiale - Claire Mitton (Revue Archéologique du Centre de la France)
The aim of this study is to present a synthesis of the Arverni’s and Vellavi’s rural sanctuaries. For that purpose, all the cult places have been recorded from archaeological data (aerial survey, field-walking, excavation) to draw the most complete synthesis. The different types of sanctuaries have been analysed and grouped in a typology, the first one for the concerned territories. Cartography and spatial analysis work has also been performed, in which the link between sanctuaries and other landscape markers has been studied.